PHÂN BỐ CÁ Ở HẠ LƯU SÔNG CÁI, THÀNH PHỐ NHA TRANG, TỈNH KHÁNH HÒA - Trần, Công Thịnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DISTRIBUTION OF FISH IN THE LOWER CAI RIVER, NHA TRANG CITY, KHANH HOA PROVINCEThe lower Cai river in Nha Trang city, which is transitional water area between the freshwater area and the marine protected area of ​​Nha Trang Bay, has an extremely important role in the socio-economic development of this region. And plays an abundant source of nutrition for coastal fish. This study was carried out at 09 sites, representing 03 watersheds (marine, brackish, and freshwater), with continuous monthly sampling from July to December 2019. The results show that the distribution of fish in the study area was influenced by time and space factors, the composition of fish species caught in the dry season was more diverse than in the rainy season, and the water near the estuary (salt water, brackish) was more diverse than the freshwater. The proportion of fish ecological groups was significantly different between sampling periods and sampling locations. Among 155 fish species recorded, 70 species have migratory phenomena to reproduce and find food. In which, the group of species moving between sea and river to find food accounts for the highest proportion with 26 species (16.8%). This result is the first scientific basis for the distribution of fish in the lower Cai River, Khanh Hoa Province, contributed to providing a data source for research, protection, and sustainable exploitation of fish resources in this area.